Pengaruh Penambahan Air Di Atas Kadar Air Optimum Terhadap Nilai CBR Dengan Dan Tanpa Rendaman Pada Tanah Lempung Yang Dicampur Abu Terbang - Puspa Ningrum; Soewignjo Agus Nugroho; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Clays are soft soil which have a low bearing capacity. One of the methods to determine the soil bearing capacity is CBR (California Bearing Ratio). Research on Laboratory for determining CBR value of soil generally performed on condition of optimum moisture content or fully saturated soil. This research evaluates the CBR value of clays with various fly ash contents from OMC to fully saturated. The results showed that, when the soil is compacted at OMC conditions, the effect of saturation resulted will decrease the CBR value up to 67% of CBR unsoaked. When soil is compacted with moisture content above the OMC, increase of water content resulted will decrease the CBR value up to 24%. Furthermore, the addition of fly ash content is effective to improve the CBR value between 20% -25%.  Key Words: CBR, water content, clay, fly ash